Assessing sexual-abuse prevention knowledge and related factors among adolescent girls with intellectual disabilities in Padang: a cross-sectional study - Arif Mansur; Meri Neherta; Lili Fajria; Ira Mulya Sari; Yelly Herien; Mutia Farlina; Putri Dwi Rusmayanti (PAGEPress Publications, 2024)
Sexual abuse among adolescents With Intellectual Disabilities (ID) has been significantly under-researched despite their high vulnerability. This study aimed to assess the sexual abuse prevention knowledge of adolescent girls with ID in Padang and explore how various respondents' characteristics relate to the risk of sexual abuse. Findings from this study may inform future prevention strategies and support services. A descriptive cross-sectional approach was utilized, and involved 50 adolescent girls from five special education schools in Padang. Respondents were assessed using the Illustrated Scale Measuring Sexual Abuse Prevention Knowledge, which covered five key domains. The study analyzed the risk of sexual abuse and related factors. The findings revealed significant knowledge disparities, especially in identifying abusive situations, with notably low scores. Statistical analysis showed a strong correlation between the disability category and additional mental or physical conditions, indicating an increased risk of sexual abuse. The results emphasize the urgent need for customized educational programs to address the specific challenges faced by adolescents with ID. Enhancing sexual abuse prevention knowledge is crucial for reducing their victimization risk. The study recommends comprehensive educational strategies and supportive interventions tailored to their cognitive and physical profiles.